The craniovertebral angle and the incidence of tension-type headache among office workers - Rienanda, Syabina Zahra; Prastowo, Bayu; Lubis, Zidni Imanurrohmah; Wibisono, Donny Septian (BKM Public Health and Community Medicine, 2025)
Purpose: This study aimed to analyze the correlation between the craniovertebral angle and the occurrence of tension-type headache among office employees. Methods: This study employed a cross-sectional, analytical observational design, involving 50 office workers selected using a stratified random sampling method. The craniovertebral angle was measured using photogrammetry with Kinovea software, and the incidence of tension-type headache was identified through the Headache Screening Questionnaire. Data were analyzed using the Spearman correlation test. Results: The average craniovertebral angle among participants was 37.2 degrees, indicating a tendency toward poor head posture. Among the workers, 30% experienced tension-type headache, 44% were considered probable cases, and 26% had no symptoms. The majority of participants spent 8 to 12 hours per day working on computers. Statistical analysis showed a significant negative correlation between craniovertebral angle and tension-type headache. Workers with lower angles—reflecting more forward head posture—were more likely to experience headaches. Although the strength of the correlation was weak, the association remained statistically significant. Conclusion: A reduced craniovertebral angle, indicating poor head posture, is associated with a higher likelihood of tension-type headache in office workers. These findings highlight the importance of implementing ergonomic interventions in the workplace to prevent posture-related health problems.